Proses Employer Branding PT. Mercedes-Benz Indonesia untuk Meningkatkan Eksistensi Perusahaan - Tasya Vicky Ryana; Hanny Hafiar; Syauqy Lukman (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2019)
Image is a public perception that’s caused by marketing communication of the organization. One of the largest automotive company in the world, Mercedes-Benz is still aware of the importance of building image with branding. Through Indonesia Most Admired Companies (IMACO) Award by the Warta Ekonomi Intelligence Unit (WEIU), companies in Indonesia compete to be superior companies compared to competitors. PT. Mercedes-Benz Indonesia, which is known to have good product knowledge among the public, is considered to have low company’s knowledge because it has not been ranked in the IMACO Award. The urgency to differentiate company with other companies as the employer encourages companies to carry out the employer branding strategy. Therefore, the author is interested in conducting further research on employer branding processes carried out by PT. Mercedes-Benz Indonesia to reach the title of the Most Admired Company. This research is a descriptive study with a qualitative data. The results of this study reveal that; 1) the formation of the employer value proposition begins with the expectations and objectives of the company that are applied in accordance with the values and corporate culture, 2) the external marketing evp is carried out by involving the general public and prospective candidates to build good image in their minds. 3) the internal marketing evp is run with employee development and engagement programs to improve their quality and capabilities.